Examining Behavioural Coping Strategies as Mediators between Work-Family Conflict and Psychological Distress - Sanaz Aazami; Khadijah Shamsuddin; Syaqirah Akmal (The Scientific World Journal)
We examined the mediating role of behavioral coping strategies in the association between work-family conflict and psychological distress. In particular, we examined the two directions of work-family conflict, namely, work interference into family and family interference into work. Furthermore, two coping styles in this study were adaptive and maladaptive coping strategies. This cross-sectional study was conducted among 429 Malaysian working women using self-reported data. The results of mediational analysis in the present study showed that adaptive coping strategy does not significantly mediate the effect of work-family conflict on psychological distress. However, maladaptive coping strategies significantly mediate the effect of work-family conflict on psychological distress. These results show that adaptive coping strategies, which aimed to improve the stressful situation, are not effective in managing stressor such as work-family conflict. We found that experiencing interrole conflict steers employees toward frequent use of maladaptive coping strategies which in turn lead to psychological distress. Interventions targeted at improvement of coping skills which are according to individual’s needs and expectation may help working women to balance work and family demands. The important issue is to keep in mind that effective coping strategies are to control the situations not to eliminate work-family conflict.